(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2019)
Optical coherence tomography is a non-invasive and label-free imaging modality based on the detection of backscattered light in samples. As microscopic OCT (mOCT) combines high axial and lateral resolution, an investigation of biological and printed samples at subcellular level is feasible. The additional excellent depth resolution enables mOCT to be a suitable quality control of 3D printed samples. The use of speckle variance adds information about cell viability. Here we present the feasibility of investigating cell viability within a cell spheroid and monitoring the cell interaction with bioprinted scaffolds using mOCT.